Analisis Efisiensi Metode Panen Manual dan Mekanisasi pada Produksi Kelapa Sawit - Hermanto Manurung; Edi Wiraguna (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Harvesting is a crucial stage in the palm oil production process that impacts the efficiency and productivity of the plantation. Choosing the right harvesting method can increase the effectiveness of time and labor. This study compares harvesting efficiency using manual and mechanized methods by measuring the duration of fruit harvest and transportation time to the collection point (TPH). This study was conducted in November–December 2024 at PT. Kencana Sawit Indonesia, located in Talao Sungai Kunyit, South Solok, West Sumatra. The equipment used included stationery, a stopwatch, and data related to working time and harvest results. Data were collected through direct observation. The analysis was carried out using the t-student statistical test to evaluate the difference in working time between the manual and mechanized methods. The results showed that harvesting with mechanization was more efficient than the manual method. The difference in harvest time reached 12 seconds per bunch with a P value of 0.0002, while the transportation time to the TPH was 23.48 minutes faster per ton with a P value <0.0001. Monthly production with mechanization averaged 48.69 tons, while the manual method only produced 38.13 tons per month. Thus, the use of mechanized harvesting methods has proven to be faster in the harvesting process, fruit transportation, and increasing monthly production results. The implementation of mechanization can be a strategic step to increase operational efficiency and productivity of oil palm plantations.